Comparison of Peri-operative and Early Oncological Outcomes of Robot-Assisted vs. Open Salvage Lymph Node Dissection in Recurrent Prostate Cancer - Devos, Gaëtan; Muilwijk, Tim; Raskin, Yannic; Calderon, Victor; Moris, Lisa; Van den Broeck, Thomas; Berghen, Charlien; De Meerleer, Gert; Albersen, Maarten; Van Poppel, Hendrik; Everaerts, Wouter; Joniau, Steven (Frontiers in Oncology, 2019)
ABSTRACT: Introduction: Salvage lymph node dissection (sLND) has been proposed as a treatment option for prostate cancer patients with lymph node (LN) recurrence following radical prostatectomy to delay or avoid palliative androgen deprivation therapy (ADT). Historically sLND has been performed using an open approach, with its associated morbidity. A limited number of studies have reported peri-operative outcomes following robot-assisted sLND. However, a direct comparison with the open approach has hitherto not yet been reported. This study investigates whether robot-assisted sLND is associated with better peri-operative outcomes compared to the open approach. Early oncological outcomes are also compared. Patients and methods: In this retrospective study, clinical data were collected from 60 patients undergoing open sLND between 2010-2016 and 30 patients undergoing robot-assisted sLND between 2016 and 2018 at our tertiary referral center. The primary objective of the study was to compare peri-operative outcomes (length of stay, estimated blood loss, operative time, intra-operative and postoperative complications) and LN yield between both procedures. As secondary objective early oncological outcome (biochemical recurrence-free survival (BRFS) and clinical recurrence-free survival (CRFS)) was compared. Variables of interest were compared using the chi-squared test (categorical variables), two sample t-test, and Mann-Whitney U test (continuous variables). To compare BRFS and CRFS, Kaplan-Meier analysis and log-rank tests were performed. Results: Robotic sLND was associated with reduced blood loss (median 100 vs. 275cc; p<0.0001) and shorter length of stay (median 2 vs. 7 days; p<0.0001) compared to open sLND. Moreover, postoperative complications within 30 days after surgery were more prevalent in the open sLND group compared to the robotic group (41.6% vs. 20%, p=0.04). No significant differences in LN yield (for each sLND template), BRFS and CRFS were detected between both groups. Conclusion: Robot-assisted sLND is associated with significantly reduced peri-operative morbidity compared to open sLND. No difference in LN yield, BRFS and CRFS was seen between both groups. Modern imaging techniques underestimate the tumor burden and therefore, the surgical sLND template should not be limited to the positive spots on pre-operative imaging.